(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A set with membership values that are vectors in the complex plane’s unit circle is called a complex fuzzy set. The capacity of the complex fuzzy set to explain both contentment and discontent, as well as the lack of confusing information in two-dimensional situations, are some of its noteworthy benefits. For this study to offer a strong and adaptable tool for complexity and uncertain circumstances, a fuzzy set and a complex fuzzy set must be combined. A novel approach to generating complex sine trigonometric reciprocal fractional floor functions from fuzzy sets is presented in this work. This work explores the usage of fuzzy sets in averaging, geometric, generalized weighted averaging and generalized weighted geometric. An aggregating model is used to determine the weighted average and geometric. Some sets with important properties will be further analyzed using algebraic approaches.